Early Stage Relapsing Polychondritis Diagnosed by Nasal Septum Biopsy - Takaaki Kobayashi; Sandra Moody; Masafumi Komori; Akira Jibatake; Makito Yaegashi (Case Reports in Medicine)
Relapsing polychondritis is a rare inflammation of cartilaginous tissues, the diagnosis of which is usually delayed by a mean period of 2.9 years from symptom onset. We present the case of a 36-year-old man with nasal pain and fever. Physical examination of the nose was grossly unremarkable, but there was significant tenderness of the nasal bridge. Acute sinusitis was initially diagnosed due to thickened left frontal sinus mucosa on computed tomography (CT); however, there was no improvement after antibiotic intake. Repeat CT showed edematous inflammation of the nasal septum; biopsy of this site demonstrated erosion and infiltration of lymphocytes, plasma cells, eosinophils, and neutrophils in the hyaline cartilage. Relapsing polychondritis was confirmed by the modified McAdam’s criteria and can be diagnosed at an early stage by nasal septum biopsy; it should be considered as a differential diagnosis in patients presenting with nasal symptoms alone or persistent sinus symptoms.